Volition and the Brain – Revisiting a Classic Experimental Study. Issue 7 (July 2018) - Frith, Chris D.; Haggard, Patrick
Abstract : In 1983 Libet et al . demonstrated that brain activity associated with a voluntary act precedes conscious experience of the intention to act by several hundred milliseconds. The implication that it is the brain, rather than 'free will', that initiates voluntary acts has been discussed ever since by philosophers and lawyers, as well as by scientists. We show here how Libet's original study gave rise to an entire research field of experimental investigations of volition.